Analysis of outcomes after revision replacement of failed total temporomandibular joint prostheses. Issue 2 (February 2020) - Gakhal, M.K.; Gupta, B.; Sidebottom, A.J.
Abstract: End-stage disease of the temporomandibular joint (TMJ) can be managed successfully with alloplastic total replacements, but these can fail because of allergy, infection, wear, fracture, and heterotopic development of bone. We prospectively reviewed the outcome data of all patients who required revision of previously placed replacement joints between 2004 and 2016. Data included pain and diet scores using 100 mm visual analogue scales (VAS), and interincisal distance recorded before, and at six weeks, six months and 12 months after operation. The reasons for failure and the number of previous procedures were also noted. Twenty patients (26 joints) had revisions. The reasons included infection (n = 9), reankylosis (n = 5), wear of the existing prosthesis (n = 2), fracture of the prosthesis (n = 2), foreign body reaction (n = 1), and allergy to the prosthesis (n = 1). The mean (range) age of the patients was 53.3 (47-68) years, and 15 were female and five male. Preoperatively, the mean (SD) pain score was 73.1 (22.4), mouth opening was 20.9 (10.2) mm, and diet score 41.7 (23.6). At 12-month follow up, all the measurements had improved significantly (p ≤ 0.05), with the pain score improving to a mean (SD) of 18.4 (25.2), mouth opening to 32.2 (9.3) mm, and diet score to 89.4 (18.5). Revision replacements done by an experienced team result in considerably improved outcomes with limited complications, but the improvements in function and pain are not as marked as they are after primary replacement.